The Effect of Overconfidence, Availability Bias and Risk Perception on Generation Z's Investment Decisions Moderated by Financial Literacy - Al Ma'ruf. S, Muhammad; Nur, Dhani Ichsanuddin; Swasti, Ika Korika (PT Larva Wijaya Penerbit, 2025)
Technological advances have an impact on several sectors, including investment use. There are several factors that can influence investment decisions. The purpose of this study is to analyze the factors of Overconfidence, Availability bias, and risk perception and financial literacy as a moderation of stock investment decisions in generation Z in Surabaya City. This study uses a quantitative approach with a sample in this study, namely generation Z from Surabaya City with an age range of 17 to 27 years, totaling 141 respondents. Data collection in this study was carried out by distributing questionnaires and then the data analysis technique used was using Partial Least Square (PLS). This study found that (1) Overconfidence contributes to stock investment decision making. (2) Availability bias contributes to stock investment decision making. (3) risk perception cannot contribute to stock investment decision making. (4) financial literacy can moderate the relationship between overconfidence and stock investment decision making. (5) financial literacy cannot moderate the relationship between availability bias and stock investment decision making. (6) financial literacy can moderate the relationship between risk perception and stock investment decision making.